CONDITIONS OF REALIZATION OF THE STATE POLICY IN THE FIELD DESHADOWING ECONOMIES ОF UKRAINE - Leonova O.O. (Pressing Problems of Public Administration, 2018)
In the current study examined the effect of the results of unof cial activity on state policy in the eld deshadowing economies and determined measures aimed at building an independent, modern,sustainable, open and competitive state on the world stage. The solution to overcome the negativeeffects of the shadow economy requires a new quality of economic relations, new institutions in thecommunity to  nd mechanisms to reduce its volume.